Tinjauan Pelaksanaan Pelepasan Informasi Medis Kepada Pihak Ketiga Untuk Klaim Asuransi di Rumah Sakit Muhammadiyah Taman Puring Jakarta Tahun 2018 - Sri Adinda; Siswati 99; Rury Agnesia (APIKES Bhumi Husada Jakarta, 2018)
ABSTRACT This study aims to determine the description of the process of release of medical information for insurance claims at Muhammadiyah Taman Puring Hospital. The research method used is a descriptive method of a survey conducted on a set of objects that usually aims to see a description of phenomena that occur within a particular population. On the implementation of medical information release and the existing Standar Operating Procedure (SOP), regarding the policy for the release of medical information, namely in the form of 6,000 stamped power of attorney, photocopy of patient identity and third party identity, there were 41 requests for medical record documents from third parties, namely 34% who did not complete. SOP should be disseminated Information Release, especially to medical record officers and customer service who are in charge of handling the release of medical information by holding socialization as well as creating an x ​​banner containing requirements for the release of medical information placed in the lobby of the hospital or near the patient registration place. It is better to provide a special room to serve the request for the release of medical information so that the direct handling is the medical record officer not through customer service so there is no communication gap between the third party and the medical record officer. Keyword: Release of Medical Information